Dollarization - Levy Yeyati, Eduardo; Sturzenegger, Federico (MIT Press, 2003)
Theoretical and empirical analysis of de jure dollarization. With the persistent instability of international financial markets, emerging economies are exploring new ways to reduce exposure to capital flow volatility. Some analysts argue that financially open economies are best served by more flexible regimes, while others argue in favor of extreme exchange rate regimes that have a strong commitment to a fixed parity or dispense with an independent currency. The successful launch of the euro has made more realistic the prospect of replacing a national currency with a strong foreign one. Recent examples include the adoption of the US dollar by Ecuador and El Salvador. The introduction of a foreign currency as sole legal tender, termed full (de jure) dollarization, has been the center of much political and academic debate. This book provides a comprehensive analysis of the issues from both theoretical and empirical perspectives. The topics discussed include the role of balance sheet effects, the linkage between currency risk and country risk, the impact of dollarization on trade, financial integration and credibility, the implications of dollarization for the lender of last resort, and the institutional and political economy aspects of dollarization.